Pendekatan Paradigma Pedagogi Refleksi dalam Kegiatan Sekami di Paroki Lewotala - Atasoge, Anselmus Dore Woho; Aran, Alfonsus Mudi (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: This study aims to show that the Reflection Pedagogy Paradigm approach helps primary school-aged children who are members of Sekami to actively engage in church life, gain a deeper understanding of their faith, and develop relevant faith life skills. By engaging children in the process of reflection, the church can create a learning environment that is inclusive, interactive, and impactful in children's spiritual development. Method: The activity model followed the dynamics of the Reflection Pedagogy Paradigm, which includes five continuous steps: context, experience, reflection, action, and evaluation.  Activities took place in the Riangkotek and Lamatou Parish of Santu Alfonsus de Liquori Riangkotek. The total number of participants included in the study was 100. Activities were conducted during the first and fourth weeks of September and October 2023. Result: The results of this activity and study show that the pedagogical approach of reflection can help Sekami to understand his role as prophet, priest and king, which are the three tasks of Jesus that must be carried out by the followers of Jesus. Through this, they can recognize and explore their abilities in the fields of religion and Catholic faith. The result of this recognition and exploration can help them gain an awareness of their role as prophets, priests, and kings. It is hoped that, through this, they will gradually become committed to growing in their Catholic faith and practicing it in their daily lives as Catholics. Limitations: This study was limited to the internal community in Riangkotek village and Lamatou Parish of Santu Alfonsus de Liquori Riangkotek. It targets the theme of the commitment of Sekami children as Catholics, and uses the paradigm approach of reflection pedagogy. Contribution: The results of this study will contribute to humanities education, religious education, and character building for elementary school children.